2018
DOI: 10.1002/etc.4164
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum hydrocarbon mixture toxicity and a trait‐based approach to soil invertebrate species for site‐specific risk assessments

Abstract: Although petroleum hydrocarbons released to the environment typically occur as mixtures, petroleum hydrocarbon remediation guidelines often reflect individual substance toxicity. It is well documented that groups of aliphatic petroleum hydrocarbons act via the same mechanism of action (nonpolar narcosis) and, theoretically, concentration addition mixture toxicity principles apply. To assess this theory, 10 standardized acute and chronic soil invertebrate toxicity tests on a range of organisms (Eisenia fetida, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…A key model assumption is that this concentration is species specific, rather than universal. Traits based studies have established differences in species responses based on lipid content, with low lipid levels linked to higher sensitivity, such as for petroleum hydrocarbons in soil invertebrates (Gainer et al, 2018) and the organophosphate fenitrothion in freshwater phytoplankton species, in which this pesticide likely exhibits narcotic toxicity (Kent and Currie, 1995). However, lipid composition currently provides only a partial explanation for the sensitivity indicated by the range of species-specific critical target lipid concentrations (Di Toro et al, 2000).…”
Section: Toxicodynamic Traits and Species Sensitivitymentioning
confidence: 99%
“…A key model assumption is that this concentration is species specific, rather than universal. Traits based studies have established differences in species responses based on lipid content, with low lipid levels linked to higher sensitivity, such as for petroleum hydrocarbons in soil invertebrates (Gainer et al, 2018) and the organophosphate fenitrothion in freshwater phytoplankton species, in which this pesticide likely exhibits narcotic toxicity (Kent and Currie, 1995). However, lipid composition currently provides only a partial explanation for the sensitivity indicated by the range of species-specific critical target lipid concentrations (Di Toro et al, 2000).…”
Section: Toxicodynamic Traits and Species Sensitivitymentioning
confidence: 99%
“…Earthworms have generally proved lower sensitivity than collembolans but higher than enchytraeids. However, Gainer et al [177] showed greater sensitivity of earthworms to lubricating mixtures including PACs and aliphatic compounds probably related to a higher uptake due to their bigger size. Deviations from nonpolar narcosis might occur for sublethal endpoints, indicating that more specific responses might be present [178].…”
Section: Effect Of Polycyclic Aromatic Compounds At Individual and Population Levelsmentioning
confidence: 98%
“…To understand how O. nitens interacts with soil contaminants, it is helpful to consider the impact of certain traits of this species, that is, its physiological, morphological, and ecological attributes (Baird and Van den Brink 2007). Specifically, 3 categories of traits are considered key to O. nitens' response to soil contamination: its body size and diet, intrinsic sensitivity, and life history characteristics (Van Straalen 1993;Rubach et al 2012;Gainer et al 2018).…”
Section: Traits Of O Nitens Influencing Toxicokinetics and Toxicodynmentioning
confidence: 99%
“…Lipid content also influences the toxicity of organic contaminants. Based on findings from Gainer et al (2018), O. nitens, like other oribatid mites, has relatively high lipid contents compared with other standardized soil invertebrates in soil ecotoxicology (Table 2), which influences the partitioning of hydrophobic organic chemicals into organisms (Belfroid et al 1996 invertebrates (Table 2). For instance, based on evidence from aquatic invertebrate studies, maternal transfer could be another excretion route for O. nitens, especially for metals and organics (Keteles and Fleeger 2001;Conley et al 2009;Cid et al 2010).…”
Section: Traits Of O Nitens Influencing Toxicokinetics and Toxicodynmentioning
confidence: 99%
See 1 more Smart Citation